Economic value of atopic dermatitis prevention via partially-hydrolyzed whey-based infant formula (PHF-W) use in high-risk, non-exclusively breastfed, Indonesian urban infants: results of a cost-effectiveness model - Marc F Botteman; Zakiudin Munasir; Astrid W Sulistomo; Erica G Horodniceanu; Abhijeet J Bhanegaonkar; Xiang Ji; Wing Yu Tang; Ray Wagiu Basrowi; Patrick Detzel (World Nutrition Journal, 2019)
Background:  Early nutritional intervention with partially-hydrolyzed whey-based formula (PHF-W) instead of standard cow’s milk formula (CMF) has been found to reduce the risk of atopic dermatitis (AD) development in non-exclusively breastfed infants with familial heredity of AD.Objective:  To estimate the 6-year economic impact of this nutritional intervention in non-exclusively breastfed Indonesian urban infants with family history of AD.Methods:  A mathematical model simulated AD incidence and burden of using PHF-W vs. CMF in the target population from birth to age 6. The model integrated literature, current cost and market catalogues, and expert clinician opinion. Modeled outcomes included AD risk, time spent post-AD diagnosis, days without flare, quality-adjusted life-years, and costs.Results: Using PHF-W instead of CMF resulted in an estimated absolute 14% (95% CI: 4%, 23%) AD risk reduction, a 0.69 year (95% CI: 0.26, 1.13) per-child reduction in time spent post-AD diagnosis, a 38 (95% CI: 12, 67) increase in days without AD flare, and a 0.046 gain in quality-adjusted life-years. The AD-related 6-year cost estimates when feeding high-risk urban infants with PHF-W were Indonesian Rupiah (IDR) 8,695,057 (95% CI: IDR 4,519,447, IDR13,995,605) and IDR13,139,569 (95% CI: IDR 7,098,794, IDR 19,216,068) per child, respectively, resulting in a net per-child difference of IDR 4,444,512 (95% CI: IDR1,893,080, IDR 8,557,946) favoring PHF-W.Conclusion: PHF-W for the first 17 weeks of non-exclusively breastfed Indonesian urban infants with a hereditary risk of AD demonstrated a reduction in AD incidence, increased days without flare, and increased quality-adjusted life-years and net cost reductions.